Significance of increasing Lorentz force and buoyancy force on the dynamics of water conveying SWCNT and MWCNT nanoparticles through a vertical microchannel. (24th May 2021) - Ramesh, G K; Manohar, G R; Venkatesh, P; Gireesha, B J
Abstract: Carbon nanotubes are used to achieve high heat transfer rates in a variety of engineering applications include thermal storage systems, electronic component cooling, high-performance building insulation, heat exchangers and drying technologies. Hence the aim of this article is to examine the addition of single walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) to water in a vertical microchannel to improve heat transfer. The effects of MHD, slip, convective boundary condition and heat source/sink are incorporated. The Brinkman-Forchheimer flow model and type II hybrid nanofluid model is adopted. Converted dimensionless differential equations are solved numerically via Dsolve command with the aid of Maple. The simulation assessment is worked out by graphs. One of the main tasks of the analysis is to compare MWCNT/water and SWCNT-MWCNT/water. It is shown that the improvement of the heat source/sink parameter improves the temperature and the rate of heat transfer in MWCNT/water is higher than SWCNT-MWCNT/water. Also larger values of Lorentz force and buoyancy force decreases the drag coefficient.